1997
DOI: 10.1007/bf02765483
|View full text |Cite
|
Sign up to set email alerts
|

New ambulatory surgical methods using an anatomical classification of urinary dysfunction improve stress, urge and abnormal emptying

Abstract: The aim of the study was to introduce an anatomical classification for the management of urinary dysfunction based on the Integral Theory, a new connective tissue theory for female incontinence. Eighty-five unselected patients, aged 27-83 years, 12 with pure stress symptoms and 73 with mixed incontinence symptoms, were classified as having laxity in the anterior, middle or posterior zones of the vagina, using specific symptoms, signs and urodynamic parameters summarized in a pictorial algorithm. Special ambula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
125
1
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(143 citation statements)
references
References 14 publications
11
125
1
4
Order By: Relevance
“…Pelvic muscles play an important part in bladder symptoms; pelvic muscle support of the bladder base and the stretch receptors control symptoms of frequency, urgency, and nocturia. Previous studies have reported a high concomitant cure rate for bladder symptoms [2]. This study confirms previous reports of high rates of improvement in symptoms of prolapse, urgency, nocturia, pelvic pain, and difficulty voiding [6].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Pelvic muscles play an important part in bladder symptoms; pelvic muscle support of the bladder base and the stretch receptors control symptoms of frequency, urgency, and nocturia. Previous studies have reported a high concomitant cure rate for bladder symptoms [2]. This study confirms previous reports of high rates of improvement in symptoms of prolapse, urgency, nocturia, pelvic pain, and difficulty voiding [6].…”
Section: Discussionsupporting
confidence: 81%
“…This procedure provides reconstruction at the three levels of connective tissue support [2]. The tape, by anchoring the apex of the prolapsed vault, supports and restores the cardinal/uterosacral ligament complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The public outcry against vaginal mesh has a valid scientific basis: the collagenous scarring that mesh creates is appropriate for nonelastic ligaments; it is contraindicated for an elastic vagina [2,3]. Ensuring any form of repair that maintains lifetime tissue elasticity is possibly crucial to success.…”
Section: Discussionmentioning
confidence: 99%
“…Major improvements in tape technology have revolutionized surgical repair of POP. These methods apply the discrete ligament repair principles so successful for the MUS [2,3] combined with site-specific repair of pubocervical, rectovaginal fascia, and extraurethral ligaments, without vaginal excision.…”
mentioning
confidence: 99%